Strategi Peningkatan Keputusan Pembelian Melalui Brand Awareness Sebagai Variabel Intervening - Rahmawati, Novia; Kurniawan, Bayu; Putri, Noventia Karina (Innovative: Journal Of Social Science Research, 2024)
Every business experiences ups and downs in sales, so this research aims to test strategies for increasing purchasing decisions through brand awareness as an intervening variable at Kedai Big Ali. This research uses the SmartPLS 4.0 program. The sample that has been determined is 96 using a non-probability sampling method, purposive sampling type. The results of data analysis show that digital marketing has no effect on brand awareness, promotion has no effect on brand awareness, innovation has an effect on brand awareness, innovation has an effect on purchasing decisions, digital marketing has no effect on purchasing decisions, brand awareness has an effect on purchasing decisions, promotion has an effect on purchasing decisions, digital marketing has no effect on purchasing decisions through brand awareness as an intervening variable, promotion has no effect on purchasing decisions through brand awareness as an intervening variable, innovation has an effect on decisions purchases through brand awareness as an intervening variable.